The Effect of Organizational Communication, Career Development, Motivation, and Work Environment on Employee Retention (Case Study at the Kosasih Rajabasa Clinic, Bandar Lampung) - Ahmad Mudabbir Pencalang; Abdul Halik; Siti Mujanah (Sean Institute, 2025)
This study aims to analyze the influence of organizational communication, career development, motivation, and work environment on employee retention in companies operating in Bandar Lampung City. The background of this study is based on the high employee turnover rate that can disrupt organizational stability and productivity. The study uses a quantitative approach with a descriptive associative research type. The study population is employees of companies operating in Bandar Lampung Regency with a minimum of one year of service. The sample was taken using a purposive sampling technique of 65 respondents. Data were collected through a structured questionnaire and analyzed using multiple linear regression with the help of statistical software. The results of the study indicate that organizational communication, career development, motivation, and work environment have a positive and significant effect on employee retention. Organizational communication and work environment factors are the main determinants in employee retention. This study recommends that companies in Bandar Lampung Regency strengthen internal communication, provide clear career development programs, increase motivation through incentives and rewards, and create a conducive work environment to improve employee retention.